2019
DOI: 10.1038/s41590-018-0289-6
|View full text |Cite
|
Sign up to set email alerts
|

Thymic regulatory T cells arise via two distinct developmental programs

Abstract: The developmental programs that generate a broad repertoire of regulatory T cells (T reg cells) able to respond to both self antigens and non–self antigens remain unclear. Here we found that mature T reg cells were generated through two distinct developmental programs involving CD25 + T reg cell progenitors (CD25 + T reg P) and Foxp3 lo T r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
206
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(227 citation statements)
references
References 57 publications
10
206
1
Order By: Relevance
“…Analysis of two discrete thymic Treg cell precursors (CD25 + Foxp3 − and CD25 − Foxp3 lo ) by scRNA‐seq has shown that they have unique transcriptional signatures that were reflective of distinct modes of differentiation 114 . The CD25 + precursors were more enriched in genes associated with stronger TCR signaling while the Foxp3 lo subset had increased expression of adapter genes that could enhance signaling via TNFRs and TCR.…”
Section: Tumor‐infiltrating T Cell Clusters Identified By Scrna‐seqmentioning
confidence: 99%
“…Analysis of two discrete thymic Treg cell precursors (CD25 + Foxp3 − and CD25 − Foxp3 lo ) by scRNA‐seq has shown that they have unique transcriptional signatures that were reflective of distinct modes of differentiation 114 . The CD25 + precursors were more enriched in genes associated with stronger TCR signaling while the Foxp3 lo subset had increased expression of adapter genes that could enhance signaling via TNFRs and TCR.…”
Section: Tumor‐infiltrating T Cell Clusters Identified By Scrna‐seqmentioning
confidence: 99%
“…White arrows depict possible further development. Mature thymic Treg populations were generated through two distinct developmental programmes involving CD25 + Treg progenitors and Foxp3 (lo) Treg progenitors . Aire expression promotes the perinatal generation of a distinct compartment of Foxp3 + Tregs that prevents autoimmunity…”
Section: The Comment On Cohn's Tritope Model and The Case For Allele‐mentioning
confidence: 99%
“…The other tTreg population is Aire ‐independent, and its generation might include bone marrow–derived thymic APCs such as plasmacytoid dendritic cells (DCs), conventional DCs and B cells . Recently, using transcriptomics, Owen et al showed two distinct progenitor tTreg populations: CD25 + Treg progenitor (TregP) that employs negative‐selection developmental programme, and Foxp3 lo TregP that co‐opted positive‐selection programme (Figure legend). It is tempting to speculate that at least one of these progenitors stems from the selection on cTECs as proposed here.…”
Section: The Dynamic Model Of Tcr V‐region Selection In the Thymusmentioning
confidence: 99%
“…IL-4 shares a number of its actions with IL-13 (Gieseck et al, 2018), a cytokine that also uses the type 2 IL-4 receptor (see below). Recently, IL-4 was suggested to contribute to Treg development (Owen et al, 2019) and to have a role in homeostasis and repair mechanisms (Harrison et al, 2019).…”
Section: Introductionmentioning
confidence: 99%